2022
DOI: 10.1097/spv.0000000000001160
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Urinary Outcomes After Transvaginal Uterovaginal Prolapse Repair With and Without Concomitant Midurethral Slings

Abstract: ImportanceMany health care providers place concomitant midurethral slings during pelvic organ prolapse repair, yet growing evidence supports staged midurethral sling placement.ObjectivesThe aim of this study was to compare urinary function after transvaginal uterovaginal prolapse repair with and without midurethral sling.Study DesignSecondary analysis of the Study of Uterine Prolapse Procedures Randomized Trial (hysterectomy with uterosacral ligament suspension vs mesh hysteropexy). Our primary outcome was Uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Table 2 illustrates the calculated difference variables between baseline and follow-up in comparison to the established minimal clinically important difference (MCID) for each domain. The calculated difference for the M-ISI severity, M-ISI SUI, M-ISI UUI, and UDI-6 domains all exceeded the established MCID, indicating clinical significance 16,17 . The other domains did not exceed the established MCID values 17–19 …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Table 2 illustrates the calculated difference variables between baseline and follow-up in comparison to the established minimal clinically important difference (MCID) for each domain. The calculated difference for the M-ISI severity, M-ISI SUI, M-ISI UUI, and UDI-6 domains all exceeded the established MCID, indicating clinical significance 16,17 . The other domains did not exceed the established MCID values 17–19 …”
Section: Resultsmentioning
confidence: 86%
“…The calculated difference for the M-ISI severity, M-ISI SUI, M-ISI UUI, and UDI-6 domains all exceeded the established MCID, indicating clinical significance 16,17 . The other domains did not exceed the established MCID values 17–19 …”
Section: Resultsmentioning
confidence: 86%
“…[6][7][8][9] Importantly, rates of postoperative SUI vary depending on preoperative continence status and the surgical procedures performed, making a universal recommendation inappropriate. [10][11][12][13] Health economic evaluations can assist in clinical decision making by adding cost, utility, and effectiveness information to the process. These are not meant to be used in isolation but can aid in the decision-making process.…”
Section: Why This Mattersmentioning
confidence: 99%
“…Others argue that an sMUS placed when indicated as a second procedure can avoid adverse events associated with sling placement such as de novo overactive bladder, mesh exposure, and urinary retention 6–9 . Importantly, rates of postoperative SUI vary depending on preoperative continence status and the surgical procedures performed, making a universal recommendation inappropriate 10–13 …”
mentioning
confidence: 99%
“…3,4 Long-term outcome studies have also demonstrated a high rate of successful treatment, with fewer than 9% of patients undergoing concomitant midurethral sling at the time of POP repair requiring subsequent retreatment for SUI. 5,6…”
mentioning
confidence: 99%